Early developmental milestones in patients with idiopathic clubfoot treated by Ponseti method - Pavone, Vito; Sapienza, Marco; Vescio, Andrea; Caldaci, Alessia; McCracken, Kathryn Louise; Canavese, Federico; Testa, Gianluca (Frontiers in Pediatrics, 2022)
Abstract Background Idiopathic clubfoot, also referred to as congenital talipes equinovarus (CTEV), is one of the most common lower limb deformities observed in newborns, leading to significant functional impairment if untreated. The aims of this study were to 1) assess the developmental milestones in patients with CTEV treated by the Ponseti technique, and to compare them to the unaffected controls; 2) evaluate the possible correlation between developmental milestones, severity of the deformity and number of casts. Materials and methods Seventy-nine subjects were divided into two groups, CTEV group (43 patients; 72 feet) and control group (36 patients). Age, sex, affected side, attainment of babbles (BAL), independent gait (IG), and combined word (CW) were recorded for all patients. In patients with CTEV, Pirani Score (PRS), number of casts (NC) and clinical outcome were collected according to the Clubfoot Assessment Protocol (CAP), The American Orthopedic Foot and Ankle Score (AOFAS), and Foot and Ankle Disability Index (FADI). Results IG was achieved later than the unaffected controls by 12/43 patients (27.9%) with CTEV and 3/36 patients in the control group (8.3%) (p = 0.04) and in a mean time of 16.8 ± 3.5 months and 13.2 ± 2.7 months, respectively (p = 0.001). In the CTEV group the mean value of CAP was 98.6 ± 4.7, of AOFAS of 98.4 ± 4.4 and of FADI equal to 99.9 ± 0.44. There were no statistically significant differences for BAL and CW; and no correlation with PRS, NC or clinical score were identified. Conclusion CTEV patients managed by the Ponseti technique achieve independent gait later than the unaffected controls, although they do so within the age limit of developmental. On the other hand, the Ponseti treatment has no impact on the attainment of language development.